Five-year results of endovascular aortic repair used according to instructions for use give a good general outcome for abdominal aortic aneurysm. (May 2019) - Unsgård, Runa G; Altreuther, Martin; Lange, Conrad; Hammer, Tommy; Mattsson, Erney
Objectives: The primary aim of this study was to investigate the rate of sac enlargement and secondary procedures after 5 years when instructions for use are strictly applied with endovascular aortic repair. The secondary aim was to investigate if strict indications with endovascular aortic repair, rendering more open operations, would change the general outcome of patients with abdominal aortic aneurysm. Materials and methods: Patients having their abdominal aortic aneurysm procedure in a single institution between 01 January 2002 and 31 December 2006 were included. Indications for endovascular aortic repair were as follows: aortic neck: length 15 mm or more, diameter 32 mm or less and straight configuration; iliac arteries: length > 10 mm, 7.5–20 mm in diameter. Sac enlargement was defined as an increase in diameter of 5 mm or more. Results: A total of 123 patients were intended to be treated electively with endovascular aortic repair from 2002 to 2007 using Cook Zenith stent grafts. In the same period, 147 patients were treated with elective open repair. At 5 years, 7.3% (N = 9) of the elective intended-to-treat patients with endovascular aortic repair had a sac enlargement. Thirty-five percent of the patients were registered with endoleaks, 13% of the patients had secondary procedures, 12.2% of the patients had early and 6.5% late complications during the follow-up period. Aneurysm rupture was seen in 1.6% of the patients. During the 5-year follow-up period, 34 (27.6%) of the endovascular aortic repair patients died. Five-year mortality for open repair was 23.8%, and 12.2% of the open repair patients had secondary procedures. Conclusion: Endovascular aortic repair for abdominal aortic aneurysm in accordance with instructions for use gives a low long-term risk for increased diameter and low rate of secondary procedures. There was similar mortality after elective endovascular aortic repair and open repair for abdominal aortic aneurysm. Applying endovascular aortic repair according to instructions for use does not seem to change the general outcome of patients with abdominal aortic aneurysm but improves the outcome with the method.